Military Police Functioning In Law Enforcement: International Experience - Kolomiets, Vladyslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The basics of functioning of the Military Law Enforcement Service in the Armed Forces of Ukraine and the necessity of bringing the military sphere of Ukraine to international requirements are investigated. The analysis of foreign experience in the organization of military police activity in the USA, France, Germany and Switzerland is carried out. Attention was drawn to the need to reform the Military Law Enforcement Service in the military police, taking into account the standards of NATO member countries in this field.